Adjacency Pair of Conversation on Interactional Discourse in High School Learning (Universitas Negeri Semarang, 2018)
In interactional discourse, the learning between teacher and students is preferably the delivery of intentions to the interlocutor. There are often implicit intentions in these interactions. The objective of this study is to describe the adjacency pair in the conversations of teacher and students in interactional discourse in high school learning. Data were collected by observation method with uninvolved conversation observation technique. Data analysis was conducted by using pragmatic methods with heuristic techniques. Based on research studies, it shows that eleven adjacency pair, including interlocutor of greeting, call-answer, complaint-aid, complaint-apologies, request-allow, request-giving information, request-offer, request-acceptance, assignment-approval, offer-acceptance, and proposal-acceptance. Practically, the research results are useful as input to teachers that there are various language characteristics of high school students that must be considered.